Conservation skills. Issue 3 (2nd September 2022) - Sloggett, Robyn
Abstract: The term 'conservation skills' is a generic, and somewhat free-floating term, that is often used interchangeably with 'manual skills', 'practical skills', 'hands-on skills' and 'treatment skills'. Giving weight to the term 'treatment skills', this article acknowledges the function of conservation treatment skills as a core conservation competency. It examines the nature of commentary that has sought to demonstrate that this competency has been reduced by a lack of focus on treatment skills in conservation education and, in turn, that this affects student skills and employability. It assesses the evidence on which this discourse has been developed, and in doing so considers the provocative and consequential nature of the discourse as it relates to conservation students and recent graduates. The article concludes that conservation, as a maturing discipline and profession, is defined by a technical, social and intellectual pluralism, and that this is more realistically the challenge for conservation education to advance in the twenty-first century.